2009
DOI: 10.1080/09670260902836246
|View full text |Cite
|
Sign up to set email alerts
|

Phytogeography ofLusitanianMacaronesia: biogeographic affinities in species richness and assemblage composition

Abstract: Analysis of biogeographic affinities is a key tool to establish and improve the resolution of hierarchical biogeographic systems. We describe patterns of species richness of the marine macroalgal flora across Lusitanian Macaronesia (Azores, Madeira, the Salvage Islands and the Canary Islands), and test (i) whether such differences are related to differences in proximity to the nearest continental shore and size among islands. We also explore biogeographic affinities in the composition of macroalgal assemblages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…The decrease of seaweed richness with isolation in the Atlantic, as detected in this study, has been found previously at a smaller scale (Tuya & Haroun, ) and is probably because of the relatively lower dispersal capacity of seaweeds (Kinlan & Gaines, ; Kinlan et al ., ). Although isolation explained seaweed richness, it was a poor predictor of fish and gastropod species richness.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The decrease of seaweed richness with isolation in the Atlantic, as detected in this study, has been found previously at a smaller scale (Tuya & Haroun, ) and is probably because of the relatively lower dispersal capacity of seaweeds (Kinlan & Gaines, ; Kinlan et al ., ). Although isolation explained seaweed richness, it was a poor predictor of fish and gastropod species richness.…”
Section: Discussionsupporting
confidence: 89%
“…Islands within oceanic archipelagos in the Atlantic show strong connectivity between their reef communities, although these archipelagos are highly isolated from other reef habitats. This results in a peculiar endemism in each archipelago and in a strong affinity of the reef biota between an archipelago's islands, so that each archipelago can be viewed as a biogeographical unit ( Avila, 2000;Floeter et al, 2008;Tuya & Haroun, 2009). Therefore, when focusing on marine shallow-water systems at an ocean-wide biogeographical scale, each of the Atlantic archipelagos can be treated as an island in studies of reef biota island biogeography.…”
Section: Study Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are congruent with the colonization of the Macaronesian Islands through a stepping-stone process, as proposed by Santos et al (1995) and Almada et al (2001). Overall, the high affinity between the ichthyofauna of the Macaronesian Islands and the west African coast parallels the biogeographic patterns found with other taxonomic groups (see Morton & Britton 2000;Tuya & Haroun 2009). …”
Section: Resultssupporting
confidence: 85%